The Impact of 9/11 on Politics and War
XVII, 264 p.
Keywords: The Impact of 9/11 on Politics and War is the first volume of the six-volume series The Day that Changed Everything? edited by Matthew J. Morgan. The series brings together from a broad spectrum of disciplines the leading thinkers of our time to reflect on one of the most significant events of our time.